Metabolomic characterisation of the glioblastoma invasive margin reveals a region-specific signature - James Wood; Stuart J. Smith; Marcos Castellanos-Uribe; Anbarasu Lourdusamy; Sean T. May; David A. Barrett; Richard G. Grundy; Dong-Hyun Kim; Ruman Rahman (Heliyon)
Isocitrate dehydrogenase wild-type glioblastoma (GBM) is characterised by a heterogeneous genetic landscape resulting from dynamic competition between tumour subclones to survive selective pressures. Improvements in metabolite identification and metabolome coverage have led to increased interest in clinically relevant applications of metabolomics. Here, we use liquid chromatography–mass spectrometry and gene expression microarray to profile integrated intratumour metabolic heterogeneity, as a direct functional readout of adaptive responses of subclones to the tumour microenvironment. Multi-region surgical sampling was performed on five adult GBM patients based on pre-operative brain imaging and fluorescence-guided surgery. Polar and hydrophobic metabolites extracted from tumour fragments were assessed, followed by putative assignment of metabolite identifications based on retention times and molecular mass. Class discrimination between tumour regions through showed clear separation of tumour regions based on polar metabolite profiles. Metabolic pathway assignments revealed several significantly altered metabolites between the tumour core and invasive region to be associated with purine and pyrimidine metabolism. This proof-of-principle study assesses intratumour heterogeneity through mass spectrometry-based metabolite profiling of multi-region biopsies. Bioinformatic interpretation of the GBM metabolome has highlighted the invasive region to be biologically distinct compared to tumour core and revealed putative drug-targetable metabolic pathways associated with purine and pyrimidine metabolism.